Adolescent Weak Decoders Writing in a Shallow Orthography: Process and Product. (2nd September 2016) - Torrance, Mark; Rønneberg, Vibeke; Johansson, Christer; Uppstad, Per Henning
ABSTRACT: It has been hypothesized that students with dyslexia struggle with writing because of a word-level focus that reduces attention to higher level textual features (structure, theme development). This may result from difficulties with spelling and/or difficulties with reading. Twenty-six Norwegian upper secondary students ( M = 16.9 years) with weak decoding skills and 26 age-matched controls composed expository texts by keyboard under two conditions: normally and with letters masked to prevent them reading what they were writing. Weak decoders made more spelling errors and produced poorer quality text. Their inter-key-press latencies were substantially longer preword, at word end, and within word. These findings provide some support for the word-level focus hypothesis, although we found that weak decoders were slightly less likely to engage in word-level editing. Preventing reading did not affect differences between weak decoders and controls, indicating that their reduced fluency was associated with production rather than reading difficulties.